Electronic Resources Forum - Managing Researcher Identity: Tools for Researchers and Librarians - Craft, Anna R. (Serials review, 2020)
Researchers have increasing opportunities to identify themselves and raise the profile of their research and scholarship through online researcher identity management and researcher profile systems. This column provides a basic introduction to researcher identity management and examines four widely used researcher profile systems: Google Scholar Citations, Open Researcher and Contributor Identifier (ORCID), Scopus Author ID, and Web of Science ResearcherID. System benefits and comparisons are provided, with the purpose of helping researchers and librarians to select appropriate researcher identity management tools to support their work.